A Multi-Agent Distributed Retrieval System - Nie, J.; Anquetil, N.; Vaucher, J. (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l’ACSI, 2013)
Various Information Retrieval techniques have been developed in the past, but none of them is perfect in every case. The MARS experimental system was built to test the integration of multiple retrieval methods in a single system in order to offer users more flexible and complementary retrieval tools. The retrieval methods integrated in MARS include not only the classical methods, but also. . .